Peningkatan Kemampuan Guru dalam Melaksanakan Penelitian Tindakan Kelas - Syamsiarna Nappu; Ratna Dewi (Universitas Negeri Makassar, 2019)
Teachers as professionals are required to always improve their competence and capabilities so that theycan teach their students as well as and as much as possible. One effort that can be done by the teacher is to improvethe quality of learning through classroom action research. This community service aims to motivate teachers in SMPNegeri 23 Makassar to carry out classroom action research and to help them improve their competence inconducting classroom action research (CAR). The service in the form of workshop provided training to t he teachersin the school which was attended by 55 teachers. The methods used are lectures, discussions, question and answer,and training. The activity includes: 1) lecturing on how to carry out a classroom action research; (2) techniques forpreparing classroom action research proposals; and (3) techniques for preparing classroom action research reports.The output of this program are: 1) the teachers are motivated and willing to develop learning innovations in schoolsthrough classroom action research and 2) the teachers make proposals and carry out classroom action research.